Dampak dan Terapi Non-Farmakologis Periodontitis pada Ibu Hamil; Kajian Literatur - Apriani, Lia Arian; Sunarjo, Lanny; Widyawati, Melyana Nurul; Wiguna, Reza Indra (Holistic Nursing and Health Science, 2022)
Introduction: According to WHO, periodontitis is a disease that affects about 20-50% of the world’s population. Periodontitis in pregnancy is often associated with poor pregnancy outcomes. Nowadays, periodontitis therapy is still giving antibiotics and mouth rinses (chlorhexidine) to reduce the dental plaque. However, these therapies have side effects in the form of antibiotic resistance, allergies and mouth irritation. Therefore, a non-conventional therapeutic that is more effective and safe is needed. Brown seaweed (Sargassum sp) is a promising alternative to its natural potential compounds as periodontitis therapy. The purpose of this study was to analyze the effect of Sargassum sp and the impact of periodontitis on pregnancy. Methods: This research is a systematic literature review by searching literature through various databases on; PubMed, Cochrane, ScienceDirect, and Google Scholar. The literature was examined in the span of 2015 to 2020. The criteria and keywords were; Sargassum and Periodontitis; Periodontitis and Pregnancy; Periodontal Disease and Pregnancy. Results: The results of this review found 12 articles that showed that periodontitis is one of the risk factors in pregnancy such as; preeclampsia, LBW, and premature. Furthermore, 9 other articles discussed the antibacterial and anti-inflammatory activity contained in Sargassum sp, which can inhibit the development of P.gingivalis and its virulence factors. Conclusion: The conclusion is metabolites of Sargassum sp “alginate” were able overcomed periodontitis in pregnancy. Thus, further research is expected to be able to intervene directly and analyze more broadly about the effect of Sargassum sp on periodontitis in pregnancy.